Approach for Diagnostic and Treatment of Achalasia - Andree Kurniawan; Marcellus Simadibrata; Prima Yuriandro; Lie Khie Chen (The Indonesian Society for Digestive Endoscopy, 2013)
Achalasia is a rare motor disorder of the esophagus and lower esophageal sphincter. The incidence is approximately 1/100,000 per year and the prevalence rate is 10/100,000. Achalasia is quite difficult to establishbecause the symptoms might be insidious and therefore not many people come to seek medical attention until it deteriorates to final stage of the disease. There are several modalities that can be used as diagnostic toolssuch as manometry, barium esophagogram, esophagoduodenoscopy, esophageal CT-scan, until the recent one, high-resolution manometry that can classify achalasia into three different types. The treatment options are the pharmacologic intervention, endoscopic treatment, minimal invasive surgery, and radical surgery.We reported a case of 20 year old female with achalasia who came with dysphagia symptom since three years before. The diagnosis was made by historytaking, physical examination and barium meal and esophagogastroduodenoscopy. The patient underwent pneumatic dilatation and since then the symptom was relieved.Keywords: achalasia, diagnostic, treatment